Food product atttributes guiding purchase choice by low-income households - Marumo, Kuda. (My University, 2009)
Background: About 66 percent of South Africans are urbanised. The majority of this population is forced by circumstances to live in informal settlements. Despite the income challenges faced, the market expenditure by these low-income consumers amounts to R129 billion per year. A lack of information exists regarding food product attributes that guide purchasing choice for maize meal. Objective of the study: To identify and describe the food product attributes experienced as most important during purchasing of maize meal by low-income consumers in informal settlements in the Johannesburg-Vaal region. Methods: Phase 1 comprised a quantitative survey in three informal! and one formal settlement (n=502), testing the level of importance perceived for 14 food product attributes. In Phase 2, focus group discussions were conducted to describe and compare the understanding of the food product attributes between groups and with literature. Results: Phase 1 defines income level as the boundary within which low-income consumers perceived the importance of food product attributes. Satiety value and the affordability of food products override sensory attributes as the main decision choice, as usually applicable to higher income groups. Nutrient content was ranked least important. These findings can probably be allocated to the need of low-income consumers to satisfy priorities for survival (satiety value). Phase 2 reported no distinctive differences in the meaning of terms between groups. However, a difference exists in the depth of meaning. The majority of descriptive elements indicated a link to economic attributes. Strong cross-links between attributes were revealed through the findings. No major differences were found in the understanding of food product attributes between the respondents' groups and with existing literature. Two concept elements, the versatility of product use as linked to taste and the ability of sensory qualities to report quality of maize meal as linked to product safety, were revealed by the current study. Key words: Food product attributes, low-income households, staple food, maize meal, informal settlement, purchase choice.
Thesis (M. Tech. (Food and Beverage management, Dept. of Hospitality, Tourism and Project Management) -- Vaal University of Technology
Keywords: Food products; Maize meal; Low-income food products; 641.30968; Food preferences.; Consumers -- Attitudes.; Food affordability